Molecular Pathways and Cellular Subsets Associated with Adverse Clinical Outcomes in Overlapping Immune-Related Myocarditis and Myositis - Bilal A. Siddiqui; Nicolas L. Palaskas; Sreyashi Basu; Yibo Dai; Zhong He; Shalini S. Yadav; James P. Allison; Rahul A. Sheth; Sudhakar Tummala; L. Maximilian Buja; Meenakshi B. Bhattacharjee; Cezar Iliescu; et al. (2024)
Abstract Immune checkpoint therapies (ICT) can induce life-threatening immune-related adverse events, including myocarditis and myositis, which are rare but often concurrent. The molecular pathways and immune subsets underlying these toxicities remain poorly understood. To address this need, we performed single-cell RNA sequencing of heart and skeletal muscle biopsies obtained from living patients with cancers treated with ICTs and admitted to the hospital with myocarditis and/or myositis (overlapping myocarditis plus myositis, n = 10; myocarditis-only, n = 1) or ICT-exposed patients ruled out for toxicity utilized as controls (n = 9). All biopsies were obtained within 96 hours of clinical presentation. Analyses of 58,523 cells revealed CD8+ T cells with a cytotoxic phenotype expressing activation/exhaustion markers in both myocarditis and myositis. Furthermore, the analyses identified a population of myeloid cells expressing tissue-resident signatures and FcγRIIIa (CD16a), which is known to bind IgG and regulate complement activation. Immunohistochemistry of affected cardiac and skeletal muscle tissues revealed protein expression of pan-IgG and complement product C4d, which were associated with the presence of high-titer serum autoantibodies against muscle antigens in a subset of patients. We further identified a population of inflammatory IL1B+TNF+ myeloid cells specifically enriched in myocarditis and associated with greater toxicity severity and poorer clinical outcomes. These results provide insight into the myeloid subsets present in human immune-related myocarditis and myositis tissues and nominate new targets for investigation into rational treatments to overcome these high-mortality toxicities. See related Spotlight by Fankhauser et al., p. 954